Incorporating Virtual Reality Training in an Introductory Public Speaking Course - Kevin Kryston; Allison Eden; Allison Eden (Central States Communication Association, 2021)
This study presents the results of two studies using a virtual reality (VR) public-speaking training simulation as an instructional aid in a basic communication course. Results from the first study suggest that VR practice was associated with higher subsequent speech delivery grades in the course compared to no practice. However, VR practice did not reduce public speaking anxiety (PSA). In a follow-up study, VR practice was compared with other forms of lab-based practice including in front of a mirror and a recorded video session. All forms of lab practice (VR, mirror, or video) were associated with higher speech grades than no practice, but there were no differences between lab-practice conditions in terms of outcomes. Results are discussed in terms of adopting and using virtual public-speaking simulations in large undergraduate public-speaking courses.